2022
DOI: 10.1186/s12879-022-07889-z
|View full text |Cite
|
Sign up to set email alerts
|

Sotrovimab use in Japanese inpatients with COVID-19: post-infusion adverse events

Abstract: Background Sotrovimab neutralizing SARS-CoV-2 remained effective at the advent of B.1 lineage of the Omicron variant in outpatients. Primarily for hospitalized patients, however, the Japanese government regulated to administer this antibody agent. As this regulation enabled close monitoring in inpatients to investigate post-infusion adverse events (AEs) and efficacy, we attempted a retrospective study while the Omicron BA.1 lineage was dominant regionally. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These analyses rarely focus on drug safety. There are few safety analyses, and these are limited by small sample sizes, reducing the ability to detect rare events (21)(22)(23)(24). A real-world safety analysis across all of England, but limited to hospital admission data, found no association between sotrovimab and 26 prespecified adverse outcomes (16).…”
Section: Discussionmentioning
confidence: 99%
“…These analyses rarely focus on drug safety. There are few safety analyses, and these are limited by small sample sizes, reducing the ability to detect rare events (21)(22)(23)(24). A real-world safety analysis across all of England, but limited to hospital admission data, found no association between sotrovimab and 26 prespecified adverse outcomes (16).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculated that patients who did not have COVID-19 antibodies due to B cell depletion would benefit from neutralizing antibodies. Sotrovimab is a neutralizing antibody designed to prevent the progression of COVID-19 [ 18 , 19 ]. A similar case report also showed that sotrovimab led to rapid improvement in two patients with persistent COVID-19 after B cell depletion [ 20 ].…”
Section: Discussionmentioning
confidence: 99%